# Hyperbola

• If the centre of the hyperbola lies at a point (h, k) and the axes are parallel to the co-ordinate axes, then the equation of the hyperbola is \tt \frac{\left(x-h\right)^{2}}{a^{2}}-\frac{\left(y-k\right)^{2}}{b^{2}}=1
• The condition for the line y = mx + c to be a tangent to the hyperbola \tt \frac{x^{2}}{a^{2}}-\frac{y^{2}}{b^{2}}=1 is that c2 = a2m2 – b2 and the co-ordinates of the points of contact are \tt \left(\pm\frac{a^{2}m}{\sqrt{a^{2}m^{2}-b^{2}}},\pm\frac{b^{2}}{\sqrt{a^{2}m^{2}-b^{2}}}\right)
• The equation of tangent to the hyperbola \tt \frac{x^{2}}{a^{2}}-\frac{y^{2}}{b^{2}}=1 interms of slope ‘m’ is \tt y = mx\ \pm\sqrt{a^{2}m^{2}-b^{2}}
• The equation of the normal to the hyperbola \tt \frac{x^{2}}{a^{2}}-\frac{y^{2}}{b^{2}}=1 at the point (x1 y1) is \tt \frac{a^{2}x}{x_{1}}+\frac{b^{2}y}{y_{1}}=a^{2}+b^{2}
• The equation of the normal to the hyperbola \tt \frac{x^{2}}{a^{2}}-\frac{y^{2}}{b^{2}}=1 at the point (a sec θ, b tan θ) is \tt \frac{ax}{\sec\theta}+\frac{by}{\tan\theta}=a^{2}+b^{2}
• The equation of normal to the hyperbola \tt \frac{x^{2}}{a^{2}}-\frac{y^{2}}{b^{2}}=1 interms of slope ‘m’ is \tt y=mx\ \pm\ \frac{m\left(a^{2}+b^{2}\right)}{\sqrt{a^{2}-b^{2}m^{2}}}
• Equation of the pair of tangents drawn from a point P(x1 y1) to the hyperbola \tt \frac{x^{2}}{a^{2}}-\frac{y^{2}}{b^{2}}=1 is SS1 = T2 where \tt S=\frac{x^{2}}{a^{2}}-\frac{y^{2}}{b^{2}}-1, S_{1}=\frac{x_{1}^{2}}{a^{2}}-\frac{y_{1}^{2}}{b^{2}}-1\ and\ T = \frac{xx_{1}}{a^{2}}-\frac{yy_{1}}{b^{2}}-1
• The equation of the chord of the hyperbola \tt \frac{x^{2}}{a^{2}}-\frac{y^{2}}{b^{2}}=1 with P(x1 y1) as its middle point is given by T = S1
• The equation of chord of contact of tangents drawn from a point P(x1 y1) to the hyperbola \tt \frac{x^{2}}{a^{2}}-\frac{y^{2}}{b^{2}}=1 is T = 0
• Eccentricity of the hyperbola \tt (e) = \sqrt{\frac{a^{2}+b^{2}}{a^{2}}}

Tricks:

• Two tangents can be drawn from a point to a hyperbola. The two tangents are real and distinct or coincident or imaginary according as the given point lies outside, on or inside the hyperbola.
• The equation of director circle of the hyperbola is x2+y2 = a2 – b2

### Latus Rectum and Examples of Hyperbola

Disclaimer: Compete.etutor.co may from time to time provide links to third party Internet sites under their respective fair use policy and it may from time to time provide materials from such third parties on this website. These third party sites and any third party materials are provided for viewers convenience and for non-commercial educational purpose only. Compete does not operate or control in any respect any information, products or services available on these third party sites. Compete.etutor.co makes no representations whatsoever concerning the content of these sites and the fact that compete.etutor.co has provided a link to such sites is NOT an endorsement, authorization, sponsorship, or affiliation by compete.etutor.co with respect to such sites, its services, the products displayed, its owners, or its providers.

1. If the centre of hyperbola is (h, k) and axes are parallel to the co-ordinate axes, then its equation is \tt \frac{\left(x-h\right)^{2}}{a^{2}}-\frac{\left(y-k\right)^{2}}{b^{2}}=1.

2.

 Imp. terms \ Hyperbola \tt \frac{x^{2}}{a^{2}}-\frac{y^{2}}{b^{2}}=1 \tt -\frac{x^{2}}{a^{2}}+\frac{y^{2}}{b^{2}}=1 \ or \ \frac{x^{2}}{a^{2}}-\frac{y^{2}}{b^{2}}=-1 Centre (0, 0) (0, 0) Length of transverse axis 2a 2b Length of conjugate axis 2b 2a Foci (± ae, 0) (0, ± be) Equation of directrices x = ± a / e y = ± b / e Eccentricity \tt e=\sqrt{\left(\frac{a^{2}+b^{2}}{a^{2}}\right)} \tt e=\sqrt{\left(\frac{a^{2}+b^{2}}{b^{2}}\right)} Length of latus rectum 2b2 / a 2a2 / b Parametric co-ordinates (a sec Φ, b tan Φ) 0 ≤ Φ < 2π (b sec Φ, a tan Φ) 0 ≤ Φ < 2π Focal radii SP = ex1 − a S'P = ex1 + a SP = ey1 − b S'P = ey1 + b Difference of focal radii (S'P - SP) 2a 2b Tangents at the vertices x = − a, x = a y = − b, y = b Equation of the transverse axis y = 0 x = 0 Equation of the conjugate axis x = 0 y = 0

3. Equations of chord joining two points P(a sec θ1, b tan θ1) and Q (a sec θ2 , b tan θ2) on the hyperbola \tt \frac{x^{2}}{a^{2}}-\frac{y^{2}}{b^{2}}= 1 is
\tt y - b tan \theta = \frac{b \tan \theta_{2}-b \tan\theta _{1}}{a \sec \theta_{2}-a \sec\theta _{1}}.\left(x-a \sec \theta_{1}\right)
or \frac{x}{a}\cos\left(\frac{\theta_{1}-\theta_{2}}{2}\right)-\frac{y}{b}\sin\left(\frac{\theta_{1}+\theta_{2}}{2}\right)=\cos\left(\frac{\theta_{1}+\theta_{2}}{2}\right)

4. Equation of chord of contact of tangents drawn from a point (x1, y1) to the hyperbola \tt \frac{x^{2}}{a^{2}}-\frac{y^{2}}{b^{2}}=1 \ is \frac{xx_{1}}{a^{2}}-\frac{yy_{1}}{b^{2}}=1.

5. The equation of the chord of the hyperbola \tt \frac{x^{2}}{a^{2}}-\frac{y^{2}}{b^{2}}=1 bisected at point (x1, y1) is given by \tt \frac{xx_{1}}{a^{2}}-\frac{yy_{1}}{b^{2}}-1=\frac{x_1^2}{a^{2}}-\frac{y_1^2}{b^{2}}or \ T=S_{1}

Equation of tangent Hyperbola
a). Point Form The equation of the tangent to the hyperbola \tt \frac{x^{2}}{a^{2}}-\frac{y^{2}}{b^{2}}=1 \ at \ \left(x_{1},y_{1}\right)is \ \frac{xx_{1}}{a^{2}}-\frac{yy_{1}}{b^{2}}=1.
b). Parametric Form The equation of the tangent to the hyperbola \tt \frac{x^{2}}{a^{2}}-\frac{y^{2}}{b^{2}}=1 \ at \ \left(a\sec \theta,b \tan \theta\right)is \ \frac{x}{a}\sec \theta -\frac{y}{b}\tan \theta =1.
c). Slope Form The equation of the tangents of slope m to the hyperbola \tt \frac{x^{2}}{a^{2}}-\frac{y^{2}}{b^{2}}=1 are given by \tt y = mx\pm \sqrt{a^{2}m^{2}-b^{2}}.
The coordinates of the point of contact are
\tt \left(\pm\frac{a^{2}m}{\sqrt{a^{2}m^{2}-b^{2}}},\pm\frac{a^{2}}{\sqrt{a^{2}m^{2}-b^{2}}}\right).

Normal Equation of Hyperbola
a). Point Form The equation of the normal to the hyperbola \tt \frac{x^{2}}{a^{2}}-\frac{y^{2}}{b^{2}}=1 \ is \frac{a^{2}x}{x_{1}}+\frac{b^{2}x}{y_{1}}= a^{2}+b^{2}.
b). Parametric Form The equation of the normal at (a sec θ, b tan θ) to the hyperbola \tt \frac{x^{2}}{a^{2}}-\frac{y^{2}}{b^{2}}=1 is ax cos θ + by cot θ = a2 + b2.
c). Slope Form The equations of the normal of slope m to the hyperbola \tt \frac{x^{2}}{a^{2}}-\frac{y^{2}}{b^{2}}=1 are given by \tt y=mx\mp\frac{m\left(a^{2}+b^{2}\right)}{\sqrt{a^{2}-b^{2}m^{2}}}